Historical Integration of Modern Urban Fabrics Using Place Making as a Tool - Jenitta Paha (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2024)
Historic sites represent the identity of the city. The rapid urbanization and city-making process have led to the decay and neglect of historical sites. To recover historical sites from the decline process, a place-making approach is used as a tool. Complex areas, with a historical urban fabric symbolizing the city's origins and often linked to important historical buildings, form the center of historical cities in India. These areas serve as a central point of identity for the entire city and are often endowed with notable heritage buildings. One such historical location in India is the coastal stretch of Manapad. The town is referred to as